Prevalence and determinants of excessive daytime sleepiness in hypertensive patients: a cross-sectional study in Douala, Cameroon. Issue 7 (29th July 2015) - Mbatchou Ngahane, Bertrand Hugo; Nganda, Motto Malea; Dzudie, Anastase; Luma, Henry; Kamdem, Félicité; Ngote, Henri Roger; Monkam, Yves; Kuaban, Christopher
Abstract : Objective: To determine the prevalence and determinants of excessive daytime sleepiness (EDS) among a group of sub-Saharan Africans living with hypertension. Design: A cross-sectional study. Setting: Cardiology outpatient unit of the Douala General Hospital in Cameroon. Participants: Patients aged 15 years and over, being followed for hypertension between 1st January and 31st July 2013. Patients with unstable heart failure, stroke and head trauma were excluded. Main outcome measure: EDS was the outcome of interest. It was defined as an Epworth sleeping scale greater or equal to 10. Logistic regression was used to identify factors associated with EDS. Results: A total of 411 patients participated in this study, with a sex ratio (male/female) of 0.58 and a mean age of 55.56 years. No patient was underweight and the mean body mass index was 30 kg/m 2 . Controlled blood pressure was found in 92 (22.4%) patients. The prevalence of EDS was 62.78% (95% CI 58.08 to 67.47). The factors independently associated with EDS were: type 2 diabetes (OR 2.51; 95% CI 1 to 6.29), obesity (OR 2.75; 95% CI 1.52 to 4.97), snoring (OR 7.92; 95% CI 4.43 to 14.15) and uncontrolled blood pressure (OR 4.34; 95% CI 2.24 to 8.40). Conclusions: A significant proportion of hypertensive patients suffer from EDS and present a high risk of sleep apnoea. Preventive measures targeted on weight loss, type 2 diabetes and snoring should be considered among these patients.